1995
DOI: 10.1111/j.1432-1033.1995.433zz.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetically Directed Fractional 13C-labeling of Proteinogenic Amino Acids. An Efficient Analytical Tool to Investigate Intermediary Metabolism

Abstract: Fux: +41 1 6 3 3 1073. Abbreviations. lD, one-dimensional ; 2D, two-dimensional; COSY, 2D correlated spectroscopy ; P22 c2-(1-76)-peptide, N-terminal polypeptide segment comprising residues 1-76 of the P22 c2 repressor; 'JXy, one-bond scalar coupling constant between carbon atoms X and Y ; isotopomer, isotope isomer; P-pyruvate, phosphoenolpyruvate; PPRibP, 5phosphoribosyl diphosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
334
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(350 citation statements)
references
References 55 publications
13
334
2
1
Order By: Relevance
“…Although similar in scope to previously described metabolic flux ratio analysis by NMR [16,17], GC-MS-based analysis provides a significant advance in handling and sensitivity, so that biomass samples as low as 1 mg cellular dry weight may be analyzed. Without the need for time-consuming quantitative physiological analysis, this methodology thus paves the road to rapid diagnosis of metabolic changes in culture volumes below 1 mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although similar in scope to previously described metabolic flux ratio analysis by NMR [16,17], GC-MS-based analysis provides a significant advance in handling and sensitivity, so that biomass samples as low as 1 mg cellular dry weight may be analyzed. Without the need for time-consuming quantitative physiological analysis, this methodology thus paves the road to rapid diagnosis of metabolic changes in culture volumes below 1 mL.…”
Section: Discussionmentioning
confidence: 99%
“…As exchange fluxes between serine and glycine [16] clearly influence the mass distribution of serine, PEP (1)2) was used to determine the fraction of trioses that were cleaved and rearranged between C 1 -C 2 by the action of transketolase, and compared to the fraction that originates from an unbroken two carbon unit of glucose according to Eqn (7). An upper bound for PEP molecules that were generated from P5P can be calculated assuming that five trioses are produced from three pentoses and that at least two trioses are rearranged by transketolase.…”
Section: Calculation Of Metabolic Flux Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…In both batch and fed-batch cultures there are increases in the biomass yield, and even after IPTG induction, cells coexpressing the PGL enzyme can sustain higher catabolic and anabolic fluxes through the PP pathway based on metabolic flux analysis estimates. Moreover, 13 C-labeling and nuclear magnetic resonance studies have shown that when cells are growing aerobically in minimal medium with glucose as the carbon source, the main biosynthetic pathway in E. coli for ribose-5-phosphate and erythrose-4-phosphate, both of which are precursors for nucleotide and aromatic amino acid biosynthesis, is the oxidative branch of the PP pathway (22). It has been reported that 22% of the glucose transported into E. coli is driven by the glucose-6-phosphate dehydrogenase and that part is diverted to nucleotide, amino acid, and vitamin biosynthesis (7).…”
Section: Figmentioning
confidence: 99%